Integrating Wordwall to Enhance Students’ Motivation and Engagement in Vocabulary Learning in EFL Classroom - mudrikah, Adila; Selvia, Sofa; Niam, Hoirotun; Suffyany, Soleh; Muharram, Muhammad Widan; Lestari R, Kenny Shania (EDUCAFL: Journal on Education of English as Foreign Language, 2026)
Vocabulary learning is widely recognized as a foundational aspect of English language proficiency, yet EFL students in Indonesia frequently struggle to remain motivated and engaged during conventional vocabulary instruction. Despite growing interest in technology enhanced learning, limited qualitative research has examined how interactive digital platforms influence observable student motivation and engagement during vocabulary learning activities. Therefore, this study aimed to explore how the integration of Wordwall influences EFL students’ motivation and engagement in vocabulary learning. Employing a descriptive qualitative research design, the study involved 19 female Grade XI students at MA Raudlatul Ulum 2, an Islamic secondary school in East Java, Indonesia. Data were collected through preliminary classroom interaction, structured classroom observation, and documentation across two instructional meetings, and analyzed using the interactive model of descriptive qualitative analysis. The findings revealed that Wordwall significantly enhanced students’ motivation and engagement, as evidenced by increased enthusiasm, active participation, peer collaboration, and self directed learning behaviors during vocabulary activities. These results indicate that game based features such as leaderboards, immediate feedback, and varied game templates effectively support intrinsic motivation and multiple dimensions of student engagement. The study contributes to the growing literature on gamification in Indonesian EFL contexts by providing a qualitative, observation based account of how Wordwall shapes the behavioral and motivational dimensions of vocabulary instruction.